Global supply chain security and management appraising programs, preventing crimes - Prokop, Darren (Butterworth- Heinemann is an imprint of Elsevier, 2017)
This book showcases industry leaders and their best practices, also exploring how the government is both a policing organization and a supply chain partner. In addition, it covers the critical roles that various technologies play, focusing on how Big Data is collected and turned into knowledge